Respostas

A melhor resposta!
  • Usuário do Brainly
2014-05-17T13:37:26-03:00
A= 1
B= -4
C= 3
Delta = (-4)² - 4x1x3
Delta = 4

x= [-(-4) +- 2]/2x1
x'= (4+2)/2 = 3
x"=(4-2)/2 = 1
1 5 1
2014-05-17T13:38:39-03:00
X²-4x+3=0   onde a=1   b=-4   c=+3


Δ=b²-4.a.c
Δ=(-4)²-4.1.3
Δ=16-12
Δ=4  ⇒ raiz quadrada de 4 é 2


x'=+4+2     6
    ¨¨¨¨¨¨¨¨¨= ¨¨¨¨¨¨  =  3
       2.1       2  


x"=+4-2       2
    ¨¨¨¨¨¨¨¨¨= ¨¨¨¨¨¨  = 2                      S:(3, 2)
      2.1        2


Espero ter colaborado, ok.
2 5 2